2021
DOI: 10.3390/ijms22084120
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism in Osteoblasts in Healthy and Pathophysiological Conditions

Abstract: Bone tissue in vertebrates is essential to performing movements, to protecting internal organs and to regulating calcium homeostasis. Moreover, bone has also been suggested to contribute to whole-body physiology as an endocrine organ, affecting male fertility; brain development and cognition; and glucose metabolism. A main determinant of bone quality is the constant remodeling carried out by osteoblasts and osteoclasts, a process consuming vast amounts of energy. In turn, clinical conditions associated with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 157 publications
1
12
0
Order By: Relevance
“…(15)(16)(17)(18)(19) More recently, glucose transporter 1 (GLUT1) has been shown to be a major transporter in primary osteoblast cultures that can modulate posttranslational modification of Runx2 by suppressing adenosine 5 0monophosphate kinase and blocking ubiquitination of Runx2. (14)(15)(16)(17)(18)(19)(20) In the current study, we implemented an in vitro "glucose-stressed metabolic model" mimicking a glucosedeficient microenvironment encountered during cell transplantation in vivo. Metabolic profiles of glucose-deprived cells and glucose-supplemented stem cells differentiated in an osteogenic differentiation medium were then compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(15)(16)(17)(18)(19) More recently, glucose transporter 1 (GLUT1) has been shown to be a major transporter in primary osteoblast cultures that can modulate posttranslational modification of Runx2 by suppressing adenosine 5 0monophosphate kinase and blocking ubiquitination of Runx2. (14)(15)(16)(17)(18)(19)(20) In the current study, we implemented an in vitro "glucose-stressed metabolic model" mimicking a glucosedeficient microenvironment encountered during cell transplantation in vivo. Metabolic profiles of glucose-deprived cells and glucose-supplemented stem cells differentiated in an osteogenic differentiation medium were then compared.…”
Section: Discussionmentioning
confidence: 99%
“…(15)(16)(17)(18)(19) These new insights have prompted the development of strategies aiming to discover novel genes that can simultaneously improve cell viability and osteogenic differentiation under ischemic conditions, thereby overcoming this major roadblock. (19)(20)(21) Although glucose uptake and aerobic glycolysis have been reported to play important roles in bone formation, (17)(18)(19)(20) reports on changes of metabolites in a glucose-deprived osteogenic microenvironment are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism enhanced the differentiation and activation of osteoclasts. Despite an increase in bone density in osteoporotic mice, the reduced bone mass was observed in healthy mice upon the blockage of glycolysis (Donat et al, 2021). The reason behind such observation might be due to the adverse effect of glycolysis blockage on new bone forming osteoblasts and osteocytes.…”
Section: Glucose Metabolismmentioning
confidence: 98%
“…Specialized osteoblast cells needed to build bone require the generation of high levels of ATP ( 23 ). Osteoblasts express 3 glucose transporters (GLUT1, GLUT3, and GLUT4) to facilitate glucose uptake ( 37 39 ). In vitro studies, including metabolic tracing with murine calvarial cells, showed that osteoblast differentiation under aerobic conditions increases glucose consumption and lactate accumulation, and that aerobic glycolysis accounts for 80% of ATP production in mature osteoblasts ( Figure 3 ) ( 40 , 41 ).…”
Section: Metabolism In Normal Bone Homeostasismentioning
confidence: 99%